Impact of Technology Integration in STEM Education - William J. Triplett (Cybersecurity and Innovative Technology Journal, 2023)
The challenge of preparing students for technology has prompted educators to increase technology in public schools. Yet despite the increased availability of technology in schools, few teachers are integrating technology for instructional purposes. Teachers must be equipped with adequate content knowledge of technology to create an advantageous learning experience in classrooms. To understand teachers’ conceptions of technology integration, this research study explored definitions and importance of STEM education in technology and individuals’ attitudes toward incorporating technology int teaching. Through a qualitative analysis, we identified existing research gaps in the field, current challenges, benefits, and implication of technology integration in science teaching after instruction.